(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Context: In the current prevalent practice at trauma centers, axial non-contrast computerized tomography scan (CT scan) is the preferred diagnostic procedure in the traumatic head injury. In many patients, a CT scan might look normal, yet the patient may have a poor Glasgow Coma Scale and have an unfavourable outcome.